1951
DOI: 10.1071/bi9510500
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Carbonic Anhydrase From Plant Sources

Abstract: Carbonic anhydrase activity in leaves of plants is low compared with that in animal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1954
1954
1979
1979

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Upon standing in the absence of cysteine the enzyme rapidly lost activity. This observation was supported by later evidence that p-chloromercuribenzoate (PCMB), iodobenzoate, and azide, all fairly specific inactivators of sulfhydryl groups, inhibit enzymatic activity in a number of different kinds of plants (Bradfield, 1947;Everson, 1970;Kiesel and Graf, 1972;Sibly and Wood, 1951).…”
mentioning
confidence: 80%
“…Upon standing in the absence of cysteine the enzyme rapidly lost activity. This observation was supported by later evidence that p-chloromercuribenzoate (PCMB), iodobenzoate, and azide, all fairly specific inactivators of sulfhydryl groups, inhibit enzymatic activity in a number of different kinds of plants (Bradfield, 1947;Everson, 1970;Kiesel and Graf, 1972;Sibly and Wood, 1951).…”
mentioning
confidence: 80%
“…Furthermore. Bradfie'ld (1947) and Sibly and Wood (1951} found that sulfanilamide at a concentration 10~^ M caused litlle or no inhibition of the aclivity of the land plant enzyme obtained from Iwo difffrenl species. The enzyme obtained from Vlmi pertusa would appear lo be different from land plants, however, since its activily is completely inhibited by low concentrations of sulfaniiamide and Diamox as is seen in Figures 3 and 4.…”
Section: Inhibitory Effects Of Siilfanilamide and Diamox On Enzyme Acmentioning
confidence: 99%
“…Plant carbonic anlhydrase is thought to be only wveaklx affected, if at all, by sulfonamides (5,9) although the literature shows s,ome variability (1,11,13,19,24). It has been found by some workers that free sulfhydryl groups are necessarv for expression of the plant enzyme or for its enhancement (1,23) but variability in this regard has ailso been reported (15,24).…”
mentioning
confidence: 99%